Effects of Long-Term Triclosan Exposure on Microbiota in Zebrafish - Tang, Ning; Fan, Pianpian; Yu, Xiaogang; Ma, Rui; Tao, Yexuan; Wang, Weiye; Ouyang, Fengxiu (Frontiers in Microbiology, 2021)
Background: Triclosan (TCS) is a widely used antibacterial agent in personal care products and ubiquitous in environment. We aimed to examine whether TCS exposure affects microbiota in gastrointestinal tract of zebrafish. Methods: After exposure to TCS 0 (Dimethyl Sulphoxide, DMSO control), 0.03, 0.3, 3, 30, 100, and 300 ng/mL, respectively, from day 0 to 120 days post fertilization (dpf), or for 7 days in adult 4-month zebrafish, the long- and short-term impact of TCS exposure on microbiome in gastrointestinal tract was evaluated by analyzing 16S rRNA gene V3-V4 region sequencing. Results: The top two most dominant microbiota phyla were Proteobacteria and Fusobacteria phylum in all zebrafish groups. In TCS exposure 0-120 dpf, compared with DMSO control, mean number of microbial operational taxonomic units (OTUs) was 54.46 lower (P < 0.0001), Chao indice 41.40 lower (P = 0.0004), and Ace indice 34.10 lower (P = 0.0044) in TCS 300 ng/mL group, but no change was observed in most of the other TCS concentrations. PCoA diagram showed that the microbial community in long-term TCS 300 ng/mL exposure group clustered differently from those in DMSO control and other TCS exposure groups. Shorter body length of zebrafish was observed in long-term TCS exposure at 0.03, 100 and 300 ng/mL. For 7-day short-term exposure in adult zebrafish, no difference was observed in alpha or beta diversity of microbiota nor the relative abundance of Proteobacteria or Fusobacteria phylum among DMSO control and any TCS levels, but minor difference in microbial composition was observed for TCS exposures. Conclusions: Long-term exposure to high TCS concentration in a window from early embryonic life to early adulthood may reduce diversity and alter the composition of microbiota in gastrointestinal tract. Effect of short-term TCS exposure was not observed on diversity of microbiota but minor change of microbial composition in adult zebrafish with TCS exposure.